2020
DOI: 10.3390/w12113271
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of Gridded Precipitation Datasets over a Sub-Region of the Central Himalaya and the Southwestern Tibetan Plateau

Abstract: Precipitation is a central quantity of hydrometeorological research and applications. Especially in complex terrain, such as in High Mountain Asia (HMA), surface precipitation observations are scarce. Gridded precipitation products are one way to overcome the limitations of ground truth observations. They can provide datasets continuous in both space and time. However, there are many products available, which use various methods for data generation and lead to different precipitation values. In our study we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 46 publications
4
13
0
Order By: Relevance
“…The results also suggest precipitation observations from valleys are not always representative of the magnitude, frequency, or seasonality of nearby high elevation regions. In addition, this further supports previous work [21][22][23]26] that highlight the importance of model resolution in capturing the magnitude, frequency and seasonality of precipitation in complex terrain. While higher-resolution models do not automatically result in improved accuracy of precipitation statistics, they have improved terrain resolution which allows for more detailed analyses of the relationship between precipitation and topography.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results also suggest precipitation observations from valleys are not always representative of the magnitude, frequency, or seasonality of nearby high elevation regions. In addition, this further supports previous work [21][22][23]26] that highlight the importance of model resolution in capturing the magnitude, frequency and seasonality of precipitation in complex terrain. While higher-resolution models do not automatically result in improved accuracy of precipitation statistics, they have improved terrain resolution which allows for more detailed analyses of the relationship between precipitation and topography.…”
Section: Discussionsupporting
confidence: 87%
“…The HAR version 2 (HARv2) is now available and provides a larger 10-km domain and improved spatial distribution of seasonal mean precipitation [25]. In an intercomparison of gridded precipitation datasets over the central Himalaya and southwestern Tibetan Plateau from May to September 2017, Hamm et al [26] found that precipitation produced by the HARv2 and a version of the HARv2 run with 2-km grid spacing (HARv2 2 km) produced a better match compared to ground-based precipitation observations than other gridded datasets. The HARv2 2-km output exhibited a slight improvement relative to observational data, including improved daily precipitation statistics due in part to the explicit rather than parameterized convection.…”
Section: Introductionmentioning
confidence: 99%
“…Using a certain threshold as a binary classifier, LTEs and NLTEs were categorized into true positive (TP), true negative (TN), false positive (FP), and false negative (FN). The Peirce skill score (PSS) (Hanssen and Kuipers, 1965) was applied as the measure of the predictive performance because it is trailindependent, which means it is unbiased even when the numbers of LTEs and NLTEs are not equally presented (Woodcock, 1976). The PSS is also known as the Hanssen-Kuiper skill score and the true skill statistic.…”
Section: Threshold Model For Atmospheric Triggersmentioning
confidence: 99%
“…It was generated by dynamical downscaling of the ERA5 reanalysis data using the Weather Research and Forecasting model (WRF). It is the only gridded atmospheric data set over High Mountain Asia with high resolution and accuracy (Hamm et al, 2020). Detailed modeling strategies of the HAR v2 are described in Wang et al (2021).…”
Section: Atmospheric Datamentioning
confidence: 99%